Laser-evoked potentials mediated by mechano-insensitive nociceptors in human skin - Dusch, Martin; Ham, Jasper van der; Benrath, Justus; Rukwied, Roman; Schmelz, Martin; Treede, Rolf-Detlef; Baumgärtner, Ulf (European journal of pain, 2016)
Objectives Laser-evoked potentials (LEP) were assessed after peripheral nerve block of the lateral femoral cutaneous nerve (LFCN) in healthy volunteers from partially anesthetized skin areas to differentially stimulate mechano-insensitive nociceptors. Methods An ultrasound-guided nerve block of the LFCN was performed in 12 healthy male subjects with Ropivacain 1%. After 30 min, the nerve block induced significantly larger anesthetic areas to mechanical stimuli than to electrical stimuli revealing an area of differential sensitivity. LEPs, reaction times and pain ratings were recorded in response to the laser stimuli of (1) completely anesthetic skin, (2) mechano-insensitive, but electrically excitable skin (‘differential sensitivity’), (3) normal skin. Results LEP latencies in the area of differential sensitivity were increased compared to unaffected skin (228 ± 8.5 ms, vs. 181 ± 3.6 ms, p < 0.01) and LEP amplitudes were reduced (14.8 ± 1.2 μV vs. 24.6 ± 1.7 μV, p < 0.01). Correspondingly, psychophysically assessed response latencies in the differentially anesthetic skin were increased (649 ms vs. 427 ms, p < 0.01) and pain ratings reduced (1.5/10 vs. 5/10 NRS, p < 0.01). Conclusion The increase in LEP latency suggests that mechano-insensitive heat-sensitive Aδ nociceptors (MIA, type II) have a slower conduction velocity or higher utilization time than mechano-sensitive type II Aδ nociceptors. Moreover, widely branched, slowly conducting and mechano-insensitive branches of Aδ nociceptors can explain our finding. LEPs in the differentially anesthetized skin provide specific information about a mechanically insensitive but heat-sensitive subpopulation of Aδ nociceptors. These findings support the concept that A-fibre nociceptors exhibit a similar degree of modality specificity as C-fibre nociceptors.
Gesehen am 03.05.2019
First published: 22 October 2015